Implikasi Hukum Asuransi Pada Transaksi Bisnis Analisis Terhadap Peraturan Dan Kepatuhan - Siregar, Fira Fadhila; Nakita, Nayla Aliffa; Febriyansah, M Ichsan; Fajriawati, Fajriawati (Inspiring Law Journal, 2024)
Along with the development of technology and information in the world, various new things appear within our daily life. One of them is the concept of buying and selling online via the internet with using e-commerce. With e-commerce, the traditional buying and selling concept brings together buyers and selling in one room has changed to the concept of long distance buying and selling or telemarketing. As is This concept, of course, both sellers and buyers will feel profitable, because of the buying and selling transactions that occur can be done 24 hours a day without being limited by certain regions. But apart from giving advantages, of course the concept of buying and selling long distance via e-commerce can also pose many risks losses, one of which is a cyber crime attack which can cause misuse of the parties' data in ecommerce resulting in losses. specifically in Indonesian laws and regulations. The research method used in writing this scientific article is method Normative legal research which aims to find a clear legal basis in placing the issues raised, in the perspective of the Commercial Code,especially those related to the issue of implementing insurance in e-commerce transactions.Based on the discussion of the research results, it is revealed that from the meaning of and restrictions on insurance in the Commercial Code, e-commerce transactions are objects that can beinsure, because all activities in e-commerce transactions can cause loss or damage to the parties involved